2009
DOI: 10.1016/s1734-1140(09)70032-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of potassium channels in the relaxant effect of levosimendan in guinea pig tracheal preparations

Abstract: We investigated both the effect of levosimendan and the role of various potassium channels in carbachol-precontracted tracheal preparations samples obtained from guinea pig. The tracheas were cut into 0.5 cm wide rings and suspended in a 20 ml organ bath. Isometric tension was continuously measured with an isometric force transducer connected to a computer-based data acquisition system. Levosimendan or cromakalim produced concentration-dependent relaxation responses in guinea pig tracheal rings precontracted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…An important finding of the present study is the strong ability of levosimendan to protect against MCh-induced bronchospasm. The bronchoprotective potential demonstrated in the present study is in accordance with earlier results obtained with isolated guinea pig tracheal rings (12). In the guinea pig study, however, levosimendan was added to an organ bath containing a tracheal ring after establishing bronchospasm.…”
Section: Systemic Circulatory Effects Of Levosimendansupporting
confidence: 92%
“…An important finding of the present study is the strong ability of levosimendan to protect against MCh-induced bronchospasm. The bronchoprotective potential demonstrated in the present study is in accordance with earlier results obtained with isolated guinea pig tracheal rings (12). In the guinea pig study, however, levosimendan was added to an organ bath containing a tracheal ring after establishing bronchospasm.…”
Section: Systemic Circulatory Effects Of Levosimendansupporting
confidence: 92%
“…Iberiotoxin, a selective blocker of BK Ca channels provoked a reduction in levosimendan-induced vasodilation in porcine coronary arteries, suggesting the involvement of BK Ca channel activation in levosimendan-induced vascular relaxation [19]. Similar combined mechanisms for smooth muscle relaxation have also been revealed in guinea pig tracheal preparations [5]. Moreover, our earlier results indicated that BK Ca channel activation was essential for OR-1896-induced coronary dilation, whereas these channels made only a limited contribution in the skeletal muscle arteries [6].…”
Section: Discussionmentioning
confidence: 90%
“…Histamine-evoked broncho-constriction is due to the activation of H 1 -histaminergic receptors and is blocked by antihistaminergic drugs such as promethazine [31,32]. Whereas, KCl-induced broncho-constriction results from the depolarization of cell membrane which causes the augmentation of calcium influx through voltage operated calcium channels leading to the rise of intracellular calcium level [33]. Moreover, the acute and relatively refractory hyperkalemia can develop.…”
Section: Discussionmentioning
confidence: 99%